Common Agency Contracting and the Emergence of "Open Science" Institutions. - David, P (American Economic Association, 1998)
The Cold War’s ending has brought mounting pressures to recognize national science and technology research systems. Yet, by comparison with what has been learned already concerning institutional arrangements and business strategies affecting corporate R&D; investments, surprisingly little is known about the economic origins and effects of the corresponding institutional infrastructures shaping the world of “academic” science, and the organization and conduct of publicly supported R&D; more generally. The desirability of closing this particular lacuna in the economics and economic-history literatures has been just as evident to economists concerned with extending the analysis of modern institutions as to those who have begun to approach the whole area of science and technology studies from the perspectives and methods of industrial-organization economics. [1] Even before the “new economics of science” had begun to direct attention to such a program, Douglass North (1990 p. 75) saw a significant challenge and a promising opportunity in explicit exploration of “the connecting links between institutional structures... and incentives to acquire pure knowledge.” The research reported here has accepted that challenge (see also the other papers in this session: Timothy Lenoir [1998], Christophe Lécuyer [1998], and Marjory S. Blumenthal [1998]). It is focused upon key episodes in the institutional evolution of “public science,” and its complex and changing relationship to the other organizational spheres of contemporaneous scientific activity: those in which research was conducted under “proprietary rules” for industrial profit-goals, and “defense-related” science and engineering knowledge was sought under conditions of restricted access to information concerning methods, findings, and their actual and potential applications.